Pharmacokinetics and Safety of Nelfinavir When Used in Combination with Zidovudine and Lamivudine in HIV-Infected Pregnant Women: Pediatric AIDS Clinical Trials Group (PACTG) Protocol 353 - Bryson, Y.J. (2008)
BACKGROUND: Combination antiretroviral regimens including nelfinavir (NFV) are commonly used in pregnancy. We studied the safety, antiviral effect, and pharmacokinetics of NFV and its M8 metabolite with two dosing regimens in combination with zidovudine (ZDV) and lamivudine (3TC) in HIV-infected pregnant women. METHOD: HIV-infected pregnant women between 14 and 34 weeks gestation received NFV (Cohort 1: 750 mg tid, n = 10; Cohort 2: 1250 mg bid, n = 23) with ZDV and 3TC. Serial blood sampling for NFV concentrations was performed antepartum (AP) and 6 weeks postpartum (PP). Maternal and cord blood samples were also obtained at delivery. NFV and M8 levels were determined by high-performance liquid chromatography. The pharmacokinetic (PK) target was an extrapolated NFV AUC(0–24) > 30 μg · h/mL. Mothers were followed frequently for potential clinical and laboratory toxicity. RESULTS: Overall, NFV in combination with ZDV and 3TC was well tolerated. The PK target was met in 3/8 AP and 5/7 PP in Cohort 1 and 17/21 AP and 16/17 PP in Cohort 2. When Cohort 2 NFV PK parameters AP and PP were compared, median C(max) (3.90 μg/mL vs. 5.01 μg/mL, p < .05) and AUC(0–24) (56.6 vs. 86.8 μg · h/mL, p < .05) were increased PP and oral clearance (Cl/F; 44.2 vs. 28.8 L/h, p < .05) was decreased PP. The average M8/NFV ratio was increased PP compared to AP (0.085 vs. 0.29, p < .001). Placental transfer of NFV was low with a median cord blood:maternal plasma ratio at delivery of 0.05. Maternal mean CD4+ T cell counts increased significantly and plasma HIV-1 RNA levels decreased from entry to delivery and 6 to 12 weeks postpartum. CONCLUSION: NFV used in combination with ZDV and 3TC was well tolerated in pregnant HIV-infected women and produced a significant improvement in HIV disease parameters. NFV drug exposure is inadequate in most pregnant women receiving 750 mg tid but is much improved with 1250 mg bid. NFV crosses the placenta poorly. The AP increase in NFV oral clearance and decrease in M8/NFV ratio suggest that CYP3A activity increases relative to CYP2C19 activity during pregnancy.